2011
DOI: 10.1186/1465-9921-12-114
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of allergic asthma: Modulation of Th2 cells and their responses

Abstract: Atopic asthma is a chronic inflammatory pulmonary disease characterised by recurrent episodes of wheezy, laboured breathing with an underlying Th2 cell-mediated inflammatory response in the airways. It is currently treated and, more or less, controlled depending on severity, with bronchodilators e.g. long-acting beta agonists and long-acting muscarinic antagonists or anti-inflammatory drugs such as corticosteroids (inhaled or oral), leukotriene modifiers, theophyline and anti-IgE therapy. Unfortunately, none o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
125
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(136 citation statements)
references
References 277 publications
2
125
0
Order By: Relevance
“…1 T cells (21) stimulate increased IgE production in B cells (22). WT mice demonstrated significantly elevated serum IgE in response to HDM ( Figure 3A) in addition to increased IL-5 and IL-13 content within the lung ( Figure 4B).…”
Section: Discussionmentioning
confidence: 99%
“…1 T cells (21) stimulate increased IgE production in B cells (22). WT mice demonstrated significantly elevated serum IgE in response to HDM ( Figure 3A) in addition to increased IL-5 and IL-13 content within the lung ( Figure 4B).…”
Section: Discussionmentioning
confidence: 99%
“…These studies combined suggest that a successful vaccine may be designed by either encapsulating the antigen inside of the particle or by adsorbing the antigen on to the surface of the particle. The shift in Th2-type response to Th1-dominant immunity during early disease has been shown to prevent allergic inflammatory responses and lung remodeling (52,53). In this study, analysis of BAL fluids (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we and others have previously demonstrated that the Th2 master transcription factor GATA-3 and Th2 cytokines IL-4 and IL-13 are positively regulated at the posttranscriptional level by HuR (21)(22)(23). Therefore, we hypothesized that HuR is coordinately regulating Th2 polarization and cytokine secretion, implicating its involvement in Th2-mediated diseases, such as allergic airway inflammation (24,25).…”
Section: Introductionmentioning
confidence: 99%